Survey of bar-lounges and restaurants regarding compliance with the current smoke-free regulation in Thulamela Municipality, South Africa - Thikolelwi R. Nemakhavhani; Henry A. Akinsola (AOSIS, 2016)
Background: The Tobacco Products Control Act, No. 83 of 1993 was introduced in South Africa in 1993. Due to the shortfalls of the 1993 Act, the Tobacco Products Control Amendment Act, No. 12 of 1999 was passed in 1999. The regulation relating to smoking of tobacco products in public places was gazetted in 2000 and implemented in 2001. Setting: The setting for the study was all selected registered licensed bar-lounges including restaurants within the municipality. Purpose of the study: To examine compliance levels with the current smoke-free regulation at bar-lounges and restaurants in Thulamela Municipality. Objectives of the study: To observe whether structural alterations had been effected to accommodate smoking patrons. To observe whether tobacco-related litter was present in nonsmoking areas and in the outdoor areas within 5 meters of windows and entry ways. To observe whether individuals or groups engaged in smoking in non-smoking areas. Methods: An observational survey was conducted to measure the level of compliance by lounges and restaurants in Thulamela Municipality. A convenience sampling method was used to sample 56 bar-lounges, including restaurants. Data were collected using an observation log. Collected data were analysed using SPSS 20.0. Results: The study findings noted low compliance with the legislation with only one establishment (1.8%) complying with the requirements of the legislation. Conclusion: The level of compliance with the legislation is in a very low state in Thulamela Municipality. Further research is needed to explore factors influencing non-compliance with the regulation. Keywords: Tobacco, legislations, compliance, restrictions, establishments, evaluation